Evaluating the awareness and effective usage of digital library consortium - Chinnasamy, K. (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
INFONET Digital Library Consortium is an innovative project launched by UGC to provide access tofull-text electronic resources and bibliographic databases to the research and academic community in India. The present paper aims to Evaluate the Awareness and Effective Usage of Digital Library Consortium: A Case Study with reference to the universities of Tamilnadu State. In this regard, the researcher has selected three universities in Tamilnadu namely Madurai Kamaraj University, Madurai, Alagappa University, Karaikudi and Bharathidasan University, Tiruchirappalli. The primary data have been collected from the Faculty Members of these three Universities with the help of Questionnaire Method. The research study encompasses independent variables mainly Designation, Age, Qualification, Teaching and Research Experience and Formal Training of respondents. This research is an attempt to examine the relationship between the variables Use of Internet and Level of Satisfaction, as two major dependent variables of the research study. To evaluate multiple effects, a set of four variables i.e. age, teaching and research experience and level of satisfaction are calculated with chi-square test analysis to see the multiple effects of the variable. The coefficient of correlation is also statistically significant by showing high positive correlation, which implies that higher the level of satisfaction, higher will be the use of Digital Library Consortium. The challenges to optimize the Digital Library Consortium services and tools and provide user education and training have been felt, posing a challenge for Library to take a lead in providing Digital Library Consortium and Information resource services